The Case of Intellectual Disability vs. the Death Penalty: A Foucauldian Analysis of Georgia’s Beyond a Reasonable Doubt Standard of Proof - Ricciardelli, Lauren A. (Critical Disability Discourses, 2019)
Georgia was the first state in the United States to ban the execution of persons with intellectual disability, and did so 14 years prior to the federal mandate in Atkins v. Virginia (2002). In doing so, it became and remains the only state to invoke the highest of standards, beyond a reasonable doubt. When states use a standard higher than the lowest of three, defendants raising the claim of intellectual disability are placed at an increased risk for rights violations that may include lack of due process, the imposition of cruel and unusual punishment, and finally, in the extinction of life. The purpose of this case study is to analyze the 2013 legislative informational hearing hosted by the Georgia House of Representatives Non-Civil Judiciary committee on the state’s standard of proof using Foucault’s medico-judicial perspective. Based on this analysis, the second purpose of the study is to propose a position of advocacy and respective strategy for changing Georgia’s standard of proof of intellectual disability. Lastly, this article recommends a strategy of leveraging the medical model of intellectual disability in the criminal justice context as an instrument for diminishing the risk for unlawful execution and enhancing the securement of accommodations while in state penal custody, as per federal law. Keywords: Intellectual disability; death penalty; medico-judicial discourse; standard of proof; beyond a reasonable doubt; impressionist narrative